¿Que es psicología? - González, Julia (Revista Chilena de Humanidades, 2015)
After presenting information on the preparatory stages, the appearance and advances of psychology as a science, the author discusses its theoretical and method:-Jlogical bases, its main tendencies and special fields of study. Shedding light on the tasks of its initiators in Chile, she presents the range of the professional fi eld of the psychologist in this country, through a list of the titlesof the papers pubLshed by the Chi·lean Review of Psychology during the years 1978, 1979 and 1980.